Building the Creativity of Bulurejo Village Community through the TASAPOT Cultivation in the Pandemic Era - Widyastuti, R A Diana; Pujisiswanto, Hidayat; Warganegara, Hayane Adeline; Sanjaya, Purba; Ramadiana, Sri (Research and Social Study Institute, 2023)
Bulurejo Village is one of the villages in Gadingrejo Subdistrict, Pringsewu Regency, Lampung Province. Bulurejo Village has a quite active Women Farmer Group (Kelompok Wanita Tani/ KWT) known as ‘Ayu Tani’, which was formed in 2014 with 27 members. Bulurejo Village is one of the villages that has the potential to develop the cultivation program of potted vegetable plants (Tanaman Sayur Dalam Pot: TASAPOT). TASAPOT cultivation is conducted to increase the consumption of various food sources in the form of vegetables with the principles of being nutritious, balanced, diverse, and healthy, so that organic farming can be applied during a pandemic era with the aim of increasing body immunity. This community services program aims to equip the community of Bulurejo Village with theoretical and practical knowledges regarding the cultivation techniques of vegetable plants in pots. The method used includes extension, discussion, mentoring, and training or direct practice in the field based on the initial evaluation as a basis for determining the knowledge level of the target partner's regarding the cultivation techniques of TASAPOT. The implementation of this community services program has succeeded to achieve the expected outcomes, namely increased knowledge of the community and members of the 'Ayu Tani' KWT in Bulurejo Village about the importance of Sustainable Food Houses (Rumah Pangan Lestari: RPL) and the cultivation techniques of TASAPOT to improve family’s health the community's standard of living. In addition, there has been an increase in partners’ understanding of the cultivation techniques of TASAPOT, starting from the benefits of utilizing the house yard, the growing media used, planting techniques, and plant maintenance until harvest.